"Reescrever minha história, virar a página, seguir em frente": trajetórias de mulheres pós-situações de violência - Borges, Érika Nunes de Medeiros Ferreira (2016)
The violence against women is a frequent problem in several life stories which marks subjectivities and memories. However, such personal experiences hardly ever are shared and heard. This research displaces to the public space of science a problem reputed to be in the private sphere of intimate relationships. Of qualitative approach, it consists of a set of five interviews with women currently living in Goiânia, who experienced the ambience of violence triggered by their partners - boyfriends or husbands. I seize the subjective meanings attributed to their experiences and I identify processes of subjectivation, with emphasis on the attempts of ressignification and resilience by the subject of the investigation, which, for its parts, points out possible ruptures with suffered violences. The study shows that, sometimes, there is a refusal to see violence as social-based process, but personal one associated with explosives and jealous behaviors. Also, the violence is displayed, in the cases investigated, as embodied, culturally contextualized and with historical specificities. Women who experienced violence remain covered by impotence, trauma, fear, psychological disorders, and lack of support of friends and family. Herewith, the study shows that even women, with high educational level and not financially dependent on their partners, have difficult to expose, denounce and seek professional help (except one who prosecuted her aggressor). The reported violence situations were not always the same, as they take different formats, in certain contexts and circumstances. However, there are common aspects shared across those women (and little less so in others), as the negative effects of violence still resonate in their lives and in whole society. Their sexist and misogynist violence survivor stories are a positive indicator whether we consider femicide the most severe end of the cycle of violence against women. Therefore, the interviews allowed to conclude that the women, who have suffered violence at the hands of their own partners, achieved to make new sense with their lives by pointing out the desire to rebuild something already –or soon to be – conquered in the narratives of them all. Their attempts to ressignification point to a shift in the balance of power, such as feminist studies underscore the theme of violence. The notion of subjectivity as an agency and not just slavery, leading to the possibility – at least in some contexts – of the strength and freedom of action.